2004
DOI: 10.1111/j.1600-079x.2004.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of melatonin as proinflammatory and antioxidant in collagen‐induced arthritis in rats

Abstract: The aim of this study was to determine the effects of melatonin on proinflammatory status of rats with collagen-induced arthritis (CIA). CIA was induced in male Wistar rats with an emulsion of type II collagen in Freund's Incomplete Adjuvant (C-II/FIA). For 14 days, control and pinealectomized rats received a subcutaneous injection of 100 microL melatonin (30 microg) or vehicle (saline on 1% ethanol). Levels of cytokines interleukin (IL)-1beta and IL-6 were determined in the serum, peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…Increase in concentration of collagen in suspension had a more significant effect on the severity of arthritis indicated by significant elevation in TNF-a levels as observed in the 4 mg/kg body weight group. TNF-a contributes to the cellular damage in arthritis [14,18]. High levels of this cytokine in circulation indicate the progression of cartilage cell injury in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in concentration of collagen in suspension had a more significant effect on the severity of arthritis indicated by significant elevation in TNF-a levels as observed in the 4 mg/kg body weight group. TNF-a contributes to the cellular damage in arthritis [14,18]. High levels of this cytokine in circulation indicate the progression of cartilage cell injury in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MRL/MP-fas lpr mice do not react appropriately to changes of the light/dark cycle, circadian melatonin rhythms seem to uncouple from the light/dark cycle, and plasma corticosterone levels are elevated during the resting phase (3). On the contrary, melatonin can also regulate the immune system (4) and can play a role in autoimmune diseases such as rheumatoid arthritis (5,6) and Crohn's disease (7).…”
mentioning
confidence: 99%
“…An additional study showed a dual effect of melatonin, which increased serum anticollagen antibodies titers together with IL-1β and IL-6 levels in serum and joints of arthritic rats, while it decreased oxidative markers in serum but not in joints. As expected, pinealectomy effects were opposed, with a reduction in antibodies, cytokine levels, and oxidative stress in joints, but elevated oxidative markers in serum [ 160 ]. In contrast to those studies supporting the deleterious effect of melatonin, a prophylactic and/or therapeutic treatment with the indoleamine reduces hind paw swelling in a similar way as indomethacin does in an adjuvant-induced arthritis model [ 161 ].…”
Section: Melatonin and Autoimmunitymentioning
confidence: 48%